2017
DOI: 10.1111/cei.13083
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing study of peripheral blood mononuclear cells in sporadic Ménière's disease patients: possible contribution of immunologic dysfunction to the development of this disorder

Abstract: To date, the pathogenesis of Ménière's disease (MD) remains unclear. This study aims to investigate the possible relationship between potential immune system-related genes and sporadic MD. The whole RNA-sequencing (RNA-seq) technology was used to analyse the transcriptome of peripheral blood mononuclear cells of three MD patients and three control individuals. Of 366 differentially expressed genes (DEGs), 154 genes were up-regulated and 212 genes were down-regulated (|log fold change| > 1 and P < 0·05). Gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 57 publications
(94 reference statements)
1
20
1
3
Order By: Relevance
“…Recent studies have found that basal levels of proinflammatory cytokines were increased in some patients with MD (55,56). Gene expression study using mRNA also demonstrated that immune-related genes such as GSTM1, TMEM176A, and TMEM176B were highly expressed in MD patients compared to normal controls (57). Through our study, the PTPN22 may be of particular interest to support the immuneassociated process in MD.…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies have found that basal levels of proinflammatory cytokines were increased in some patients with MD (55,56). Gene expression study using mRNA also demonstrated that immune-related genes such as GSTM1, TMEM176A, and TMEM176B were highly expressed in MD patients compared to normal controls (57). Through our study, the PTPN22 may be of particular interest to support the immuneassociated process in MD.…”
Section: Discussionsupporting
confidence: 62%
“…The risk of Meniere's disease is greater in patients with a history of head trauma, including fractures of the skull base, labyrinthitis, or syphilis. Autoimmune disorders, including HT, remain a potential mechanism for some cases of Meniere's disease [45][46][47][48][49]. Tamura (1964) was the first to find the correlation between Meniere's disease and autoimmune diseases [10] and assumed that in patients with Meniere's disease, hypothyroidism could be involved in the increase in the fluid pressure in the inner ear and, consequently, the development of endolymphatic hydrops.…”
Section: Meniere's Diseasementioning
confidence: 99%
“…Their REVIEW studies confirmed statistically higher serum levels of anti-TPO and anti-TG antibodies in patients with Meniere 's disease compared to groups of patients with vestibular disorders other than endolymphatic hydrops. Anti-TPO and anti-TG antibodies could reach the structures of the inner ear through the blood vessels, and due to the reaction with the cells of the endolymphatic sac they could increase endolymphatic pressure in the inner ear [45][46][47][48][49]. However, the precise mechanisms of this process have not been confirmed yet and are still hypothetical.…”
Section: Meniere's Diseasementioning
confidence: 99%
See 2 more Smart Citations